(untitled) (Eurasian Journal of Learning and Academic Teaching, 2023)
This article provides detailed information about the reforms in the field of culture and art in the Republic of Uzbekistan, the analysis of the life, creative activity and works of the people’s artist of Uzbekistan Kamoliddin Rakhimov, one of the representatives of the traditional singing art of Namangan region